Analyse The Stock Movement Trend Using Candlesticks Chart ‎and The Risk & Volatility Associated - Selected Large-Cap ‎Stocks in The IT Sector - D, Paranichandran; Ilankadhir , Dr. M (International Journal of Accounting and Economics Studies, 2025)
This study investigates the prediction of stock movement trends, risk, and volatility associated with large-cap IT sector stocks on the Na-‎National Stock Exchange (NSE) using candlestick charts. By focusing on the top five companies in the Nifty IT index—Infosys Ltd, Tata ‎Consultancy Services, Tech Mahindra Ltd, HCL Technologies Ltd, and Wipro Ltd—this research aims to provide a comprehensive analysis ‎of market behaviour over two years (April 2022 to March 2024). Utilising technical analysis, the study examines beta coefficients to measure volatility and sensitivity to market changes, as well as standard deviation to assess risk. Findings indicate that these stocks exhibit moderate volatility and are generally less risky investments. The study also highlights the significance of support & resistance and the Relative ‎Strength Index(RSI) levels in predicting market trends and provides strategic insights for investors. Despite a small sample size, the ‎search offers valuable insights into stock performance in the IT sector, paving the way for further studies with larger samples and comparative analyses. The results suggest that informed technical analysis can enhance investment decisions in the volatile financial market, emphasizing the importance of remaining attuned to market dynamics and leveraging technical tools for high accuracy in price prediction and profitability‎.